The organic chem lab survival manual : a student's guide to techniques - Zubrick, James W (John Wiley, 2011)
Praise for The Organic Chem Lab Survival Manual "This manual is the best thing since sliced bread for learning initial techniques for organic lab. Clearly, this author has dealt with students in the organic lab for a long time..the writing style is wonderful, incredibly appropriate for college undergrads." - Deborah Lieberman, University of Cincinnati "Organic Chemistry lab can be quite intimidating to students. Zubrick helps make organic chemistry a little less scary." - DeeAnne Goodenough-Lashua, the University of Notre Dame "The manual is a must for students who really want to understand what they are doing...The writing style is outstanding and approachable for the novice. Overall, it is an outstanding text for the general organic chemistry laboratory." - Robert Stockland, Bucknell University "I love Zubrick's style: it's funny, engaging, and friendly...the student will probably find the book entertaining (I do), and learn about organic chemistry lab at the same time. I highly recommend it." - Peter T. Bell, Tarleton State University "I have used Zubrick since the fourth edition was released and have noticed that each subsequent edition gets better and better." - Christopher J. Peeples, The University of Tulsa